The prophet hud and the storm - Khan, Saniyasnain (Goodword Kidz Place of publication not identified, 2003)
The Prophet Hud and the Storm is a powerful story that illustrates the themes of faith, resilience, and divine justice as Prophet Hud guides his people through trials and a catastrophic storm, emphasizing the importance of obedience to God.